Hedge Funds and Systemic Risk - Dixon, Lloyd (RAND Corporation, 2012)
This report explores the extent to which hedge funds create or contribute to systemic risk, the role they played in the financial crisis, and whether and how the Dodd-Frank Wall Street Reform and Consumer Protection Act of 2010 addresses the potential systemic risks posed by hedge funds.